Rhinovirus bronchiolitis, maternal asthma, and the development of asthma and lung function impairments. Issue 2 (24th November 2020) - Da Silva Sena, Carla R.; Morten, Matthew; Meredith, Joseph; Kepreotes, Elizabeth; E. Murphy, Vanessa; G. Gibson, Peter; D. Robinson, Paul; D. Sly, Peter; Whitehead, Bruce; Karmaus, Wilfried; Collison, Adam; Mattes, Joerg
Abstract: Background: Children with a history of rhinovirus (RV) positive bronchiolitis have a high risk of developing subsequent asthma. Maternal asthma might also increase this risk. The aim of this study was to investigate the combined effects of hospitalization for RV positive bronchiolitis in infancy and a history of maternal asthma on the development of asthma at preschool age. Methods: This is a prospective cohort study of 139 preschool‐aged children, with a history of hospital admission for bronchiolitis in infancy, followed‐up to ascertain asthma and asthma‐like symptoms, skin prick allergy test positivity, and lung function measured pre‐ and post‐bronchodilator using impulse oscillometry. Results: Children with a past hospitalization for RV positive bronchiolitis (42.4% of all) and a history of maternal asthma (36.7% of all) had the greatest prevalence and risk ratio (RR) for doctor‐diagnosed asthma (prevalence 81.8% and RR 2.10, 95% confidence interval [CI] 1.37–3.19, p  = .001), use of inhaled corticosteroids (68.2% and RR 2.17, 95% CI 1.19–3.99, p  = .001) and short‐acting β‐agonists in the last 12 months (95.2% and RR 1.49, 95% CI 1.17–1.89, p  = .001), as compared to those with RV negative bronchiolitis and no maternal asthma history. More children in this group had an abnormal airway resistance (33.3% and adjusted risk ratio [aRR] 3.11, 95% CI 1.03–9.47, p  = .045) and reactance (27.8% and aRR 2.11, 95% CI 1.06–4.26, p  = .035) at 5 Hz, as compared to those with RV negative bronchiolitis and no maternal asthma history. Conclusion: Hospitalization for RV positive bronchiolitis in early life combined with a history of maternal asthma identifies a subgroup of children with a high asthma burden while participants with only one of the two risk factors had intermediate risk for asthma.